Age of onset and lifetime projected risk of psychotic experiences: Cross-national data from the world mental health survey (2020)
Background: Given the early age of onset (AOO) of psychotic disorders, it has been assumed that psychotic experiences (PEs) would have a similar early AOO. The aims of this study were to describe (a) the AOO distribution of PEs, (b) the projected lifetime risk of PEs, and (c) the associations of PE AOO with selected PE features. Methods: Data came from the WHO World Mental Health (WMH) surveys. A total of 31 261 adult respondents across 18 countries were assessed for lifetime prevalence of PE. Projected lifetime risk (at age 75 years) was estimated using a 2-part actuarial method. AOO distributions were described for the observed and projected estimates. We examined associations of AOO with PE type metric and annualized PE frequency. Results: Projected lifetime risk for PEs was 7.8% (SE = 0.3), slightly higher than lifetime prevalence (5.8%, SE = 0.2). The median (interquartile range; IQR) AOO based on projected lifetime estimates was 26 (17-41) years, indicating that PEs commence across a wide age range. The AOO distributions for PEs did not differ by sex. Early AOO was positively associated with number of PE types (F = 14.1, P < .001) but negatively associated with annualized PE frequency rates (F = 8.0, P < .001). Discussion: While most people with lifetime PEs have first onsets in adolescence or young adulthood, projected estimates indicate that nearly a quarter of first onsets occur after age 40 years. The extent to which late onset PEs are associated with (a) late onset mental disorders or (b) declining cognitive and/or sensory function need further research.